The Strategy of Improving Complaint Management in Surakarta City Toward Society 5.0-Based Public Service - Hana Ni’ma Rosida; Kristina Setyowati (Indonesian Association for Public Administration (IAPA), 2021)
The organization of public service is not free of public critique. The management of complaint is a factor that can improve public service quality. Complaining is important because it is the public’s expression that can result from public dissatisfaction with a product or a service. Moreover, to deal with Society 5.0 era, the government should provide a system to solve the problem. Therefore, this research aims to discuss the strategies taken by Surakarta City Government in managing complaint in Surakarta City toward a society 5.0-based public service. This research employed a qualitative research method. Technique of analysis used in this study was content analysis technique obtained through literature review. Based on the result of literature review, it can be seen that some strategies have been taken by Surakarta City Government, including, among others: improving the quality of human resource constituting public apparatuses; making policy; and providing complaining media.